Permasalahan Ta'lil Al-Ahkam Sebagai Asas Penerimaan Maqasid Al-Shari'ah Menurut Ulama Usul - Ahmad, Ridzwan (Jurnal Fiqh, 2008)
Ta?lil al-ahkam is the main problem that leads to the difference amongst the Usuliyyun in relating the Islamic rulings with maslahah. Theoretically, there are disagreements between the jurists in their attempt to relate Islamic rulings with maslahah. However, in practice, almost all jurists except the Zahiris consider maslahah as the main foundation in contemporary Islamic rulings. As as consequence of a long contention in Islamic philosophy (?ilm al-kalam), especially in the notion of good (al-tahsin) and bad (al-taqbih), the discussion on ta?lil al-ahkam was mixed with philosophy which resulted in the situation where maqasid al-syariah is not quite suitable as the basis to unify the various opinions of the jurists. This article attempts to discuss the position of ta?lil al-ahkam according to the jurists and its relationship with maqasid al-shari?ah. Moreover, the author tries to deliberate the status of ta?lil al-ahkam in the perspectives of the usuliyyun notwithstanding the various contentions pertinent to it.